The ultrastructure of spermatid development during spermiogenesis within the rosebelly lizard, Sceloporus variabilis (Reptilia, Squamata, Phrynosomatidae). (4th November 2013) - Gribbins, Kevin M.; Matchett, Caroline L.; DelBello, Kathryn A.; Rheubert, Justin; Villagrán‐SantaCruz, Maricela; Granados‐González, Gisela; Hernández‐Gallegos, Oswaldo
ABSTRACT Several recent studies have mapped out the characters of spermiogenesis within several species of squamates. Many of these data have shown both conserved and possibly apomorphic morphological traits that could be important in future phylogenetic analysis within Reptilia. There, however, has not been a recent study that compares spermiogenesis and its similarities or differences between two species of reptile that reside in the same genus. Thus, the present analysis details the changes to spermiogenesis in Sceloporus variabilis and then compares spermatid morphologies to that of Sceloporus bicanthalis. Many of the morphological changes that the spermatids undergo in these two species are similar or conserved, which is similar to what has been reported in other squamates. There are six main character differences that can be observed during the development of the spermatids between these two sceloporid lizards. They include the presence (S. variabilis) or absence (S. bicanthalis) of a mitochondrial/endoplasmic reticulum complex near the Golgi apparatus during acrosome development, a shallow (S. variabilis) or deep (S. bicanthalis) nuclear indentation that accommodates the acrosomal vesicle, filamentous (S. variabilis) or granular (S. bicanthalis) chromatin condensation, no spiraling (S. variabilis) or spiraling (S. bicanthalis) of chromatin during condensation, absence (S. variabilis) or presence (S. bicanthalis) of the longitudinal manchette microtubules, and the lack of (S. variabilis) or presence (S. bicanthalis) of nuclear lacunae. This is the first study that compares spermiogenic ultrastructural characters between species within the same genus. The significance of the six character differences between two distantly related species within Sceloporus is still unknown, but these data do suggest that spermiogenesis might be a good model to study the hypothesis that spermatid ontogeny is species specific. J. Morphol. 275:258–268, 2014. © 2013 Wiley Periodicals, Inc.